2010
DOI: 10.1510/icvts.2009.229617
|View full text |Cite
|
Sign up to set email alerts
|

Off-pump versus on-pump coronary artery revascularization: effects on pulmonary function

Abstract: Many studies have shown important changes in lung function tests after coronary artery surgeries. It is controversial if off-pump surgery can give a better and shorter recovery than the on-pump. A prospective study was conducted on 42 patients submitted to coronary artery surgery and divided into two groups: 21 off-pump using intraluminal shunt (G (I)) and 21 on-pump (G (II)), matched by the anatomical location of the coronary arteries lesions. All patients had spirometric evaluation, blood gas measurements an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 14 publications
2
12
0
2
Order By: Relevance
“…Other studies previously showed that less invasive surgical approaches to cardiac surgery have advantages over the standard median sternotomy in terms of postoperative pulmonary function and the recovery of pulmonary status [2, 3]. These reports presented similar results to our study.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Other studies previously showed that less invasive surgical approaches to cardiac surgery have advantages over the standard median sternotomy in terms of postoperative pulmonary function and the recovery of pulmonary status [2, 3]. These reports presented similar results to our study.…”
Section: Discussionsupporting
confidence: 91%
“…This would suggest that faster mobilisation and more efficient early recovery of pulmonary function are more likely for patients who have had minimally invasive RT-AVR surgery [3]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Guizilini et al [8] demonstrated that patients underwent off-pump surgery had better preservation of pulmonary function when compared to those on-pump. Recently, Silva et al [12] demonstrated that significant deterioration in lung function occurs following either on-and off-pump CABG. However, a greater decrease was found in patients undergoing onpump CABG.…”
Section: Data Expressed As Mean ± Standard Deviation P Values For Comentioning
confidence: 99%